ROH-ROH YANG TERPENJARA DALAM 1 PETRUS 3:18-21 - Alfonso Tarigan (Jurnal Koinonia, 2015)
Dealing with the identity of, the location of the spirits which areimprisoned in 1 Peter 3:18-21, and the time when Jesus went and preached to themhave been disputed among the scholars. The paper tries to see the disputedmatters from the view points of the literary structure of the texts, the grammaticaland syntactical relation of the texts, the broader theological meaning, andimplications as well.From the points of view of the literary structure of the texts shows thatthe author of the book wants his readers that even though they have to suffer, theyshould be suffering because of right things, and should not be because of their ownfaults.According to grammatical and syntactical analysis, it is found that thephrase “in which” referring to Jesus before His incarnation. In analyzing thephrase “spirits in prison” in the light of the immediate context in 1 Peter 3:19, thetext clearly indicates that it refers to the spiritual prison instead of literal prison.The Bible simply teaches that someone has to receive or reject salvationwhile he or she is still alive; because the probation for human is ended when he orshe dies. There is no second chance to accept salvation after the present life.Jesus wants human being does not only escape from the present worldlysuffering, but also he wants to release humanity from the greater suffering, that isthe eternal lost.This study concludes that before His incarnation, Jesus was in the spirit,and the spirit of Christ had inspired the prophet Noah as well as other ancientprophets. The expression “spirits in prison” denotes to the evil people who wereliving before the coming of the diluvian who did not believe and reject themessage given by the prophet Noah.